Associação entre consumo alimentar e perpetração de bullying entre adolescentes brasileiros - Okada, Letícia Martins (2023)
Introduction: Previous studies have assessed the association between food consumption and bullying perpetration, but most of them have not assessed dietary patterns or specified different forms of bullying. Furthermore, the role of deviant behaviors as a possible mediator of this association is still unclear. Objectives: To evaluate the association between dietary patterns with bullying roles and its different types of perpetration (Article 1), as well as to evaluate the mediating effect of deviant behaviors in the association between the ultra-processed dietary pattern and bullying perpetration, in Brazilian adolescents (Article 2). Methods: Data from the Sao Paulo Project for the social development of children and adolescents (SP-PROSO) were used, referring to a representative sample of 9th grade students of middle school, from public and private schools in Sao Paulo (n=2.680). Through exploratory factor analysis and considering the frequency of consumption in the last week to the survey of several food, healthy and unhealthy dietary patterns (Article 1) and the ultra-processed dietary pattern (Article 2) were obtained, considered as exposures. Outcomes were bullying role (victim-only, bully-only, bully-victim) and bullying perpetration (any type, social exclusion, psychological/verbal aggression, physical aggression, property destruction, sexual harassment). Deviant behaviors (mediator) were assessed through a score. Multinomial and logistic regression models were performed for the total sample and stratified by sex (only for association with sexual harassment), adjusting for covariates (Article 1). Mediation analyzes were performed through logistic regression using the KHB method (Article 2). Results: Adolescents who had a healthy dietary pattern were less likely to be bullies (RR: 0.67 95%CI=0.49-0.92), while adolescents with an unhealthy dietary pattern were more likely to be bully-victims (RR: 1.29 95%CI=1.12-1.48). The unhealthy dietary pattern was associated with any type of bullying (OR: 1.24 95%CI=1.12-1.38), mainly with sexual harassment (OR: 1.71 95%CI=1.13-2.60) and physical aggression (OR: 1.52 95%CI=1.18-1.95). Boys with an unhealthy dietary pattern were more likely to sexually harass another adolescent (OR: 2.10 95%CI=1.20-3.66). The mediating effect of deviant behaviors was found in the association of the ultra-processed dietary pattern with all types of perpetration, with a high mediation percentage for psychological/verbal aggression (40.1%). A small positive mediating effect of deviant behaviors was observed in the association of ultra-processed dietary pattern with physical aggression (18.3%) and property destruction (18.2%), which means that these associations have other mediators, in addition to deviant behaviors (significant direct effect). Conclusions: Adolescents who had a healthy dietary pattern were less likely to perpetrate bullying. The unhealthy dietary pattern was associated with bullying perpetration, especially with sexual harassment by boys. The association between the ultra-processed dietary pattern and bullying perpetration may occur via deviant behaviors. For physical aggression and property destruction, the deviant behaviors had a positive effect on bullying, but this effect explained only a small portion of the total effect of such association.